Exploring in vitro and in silico Biological Activities of Calligonum Comosum and Rumex Vesicarius: Implications on Anticancer and Antibacterial Therapeutics - Sahar S. Alghamdi; Raghad A. Alshafi; Sarah Huwaizi; Rasha S. Suliman; Afrah E. Mohammed; Zeyad I. Alehaideb; Allulu Y. Alturki; Sara A. Alghashem; Ishrat Rahman (Elsevier, 2023)
Introduction: The adverse effects of clinically used anti-cancer medication and the rise in resistive micro-organisms have limited therapeutic options. Multiple anti-cancer drugs are derived from medicinal herbs which also have shown anti-bacterial effects. This study aimed to identify the optimal extraction solvent for detecting the cytotoxic and anti-bacterial effects of Calligonum comosum (C. Comosum) and Rumex vesicarius (R. Vesicarius) extracts. Additionally, the study aimed to identify active metabolites and assess their potential as future drug candidates for anti-cancer and anti-bacterial therapeutics. Methods: Leaves from both plants were extracted using ethanol, ethyl acetate, chloroform, and water. The cytotoxic effects of the extracts were tested on liver, colon, and breast cancer cell lines. Apoptosis was assessed using High Content Imaging (HCI) and the ApoTox triplex Glo assay. The anti-bacterial effects were determined using agar-well diffusion. Liquid chromatography-mass spectrometry (LC-MS) was used to tentatively identify the secondary metabolites. In silico computational studies were conducted to determine the metabolites' mode of action, safety, and pharmacokinetic properties. Results: The ethanolic extract of C. Comosum exhibited potent cytotoxicity on breast cancer cell lines, with IC50 values of 54.97 μg/mL and 58 μg/mL for KAIMRC2 and MDA-MB-231, respectively. It also induced apoptosis in colon and breast cancer cell lines. All tested extracts of C. Comosum and R. Vesicarius demonstrated anti-bacterial activity against Staphylococcus aureus and Escherichia coli. Seven active metabolites were identified, one of which is Kaempferol 3-O-Glucoside-7-O-Rhamnoside, which showed strong (predicted) anti-cancer activity. Kaempferol 3-O-Glucoside-7-O-Rhamnoside and Quercetin-3-O-Glucuronide also exhibited potential anti-bacterial effects on gram-positive and negative bacteria. Conclusion: Ethanol extraction of C. Comosum solubilizes active metabolites with potential therapeutic applications in cancer treatment and bacterial infections. Kaempferol 3-O-Glucoside-7-O-Rhamnoside, in particular, shows promise as a dual therapeutic drug candidate for further research and development to improve its efficacy, safety, and pharmacokinetic profile.